TERMINOLOGI TA’DIB DALAM PERSPEKTIF SYED MOHAMMAD NAQUIB AL-ATTAS - Abdul Rosyad; Wasehudin (Bajang Institute, 2022)
This paper tries to discuss the concept offered by Al-Attas. His thinking is seen as fundamental because the concept is different from the terms that are already popular in the world of Islamic education. According to Al-Attas, the right concept for Islamic education is Ta'dib, not Tarbiyah or Ta'lim. Because ta'dib already includes the meaning of tarbiyah and ta'lim. Tarbiyah termsAs a concept of education, according to him, it is not appropriate to show education in the meaning of Islam, because education in Islam is intended only for humans while tarbiyah includes humans and others. While the word ta'lim has a special connotation and refers to